Is the right to health undermined by the agreement of trade-related aspects of intellectual property rights? / Helmi Khair - Khair, Helmi (Universiti Teknologi MARA, Negeri Sembilan, 2016)
This article aims to provide a brief overview of the Agreement of Trade-Related Aspects of Intellectual Property Rights (TRIPS). The analysis will be focused on the agreement itself, its flexibilities, and its impacts on the right of access to affordable medicine. Particularly on medicines which are still under patent protection, a standardised protection period of the same, and the inclusion of pharmaceutical products within the ambit of patentable subject matter is arguably affecting one’s right to access to affordable medications. Further, the clash of interests i.e between patent holders (mostly, big pharmaceutical companies) and affected people (mainly, patients and their family) is highly likely to happen – especially in poor and developing countries. This paper seeks to assess whether the right to health is undermined by the TRIPS Agreement, and the analysis finds that such right is not adversely affected by the same.